Dijon, « ville sur la Saône ». Frontières urbaines, réseaux d’eau potable et territoires de la ressource en eau - Sandrine Petit (Pôle de Recherche pour l'Organisation et la diffusion de l'Information Géographique, 2021)
According to their needs, cities extend their borders to neighboring territories. This is the case for the supply of drinking water. Like other cities, Dijon has depended on external resources since 1939. The water table of the Saône became a key resource for its development. Thanks to the hydraulic infrastructures, the city extended its borders and created a sovereignty over the communes of its periphery with which it traded water. Decentralization laws gave it new prerogatives over the sustainable management of watershed resources, a challenge to be met in the context of climate change. The reticular and spatial extension of the city is sometimes questioned or even contested by other actors: some municipalities seeking water autonomy or the Department of Côte d’Or.